Efektivitas Pelaksanaan Diversi dalam Penyelesaian Perkara Anak sebagai Pelaku Penganiayaan dan Pengeroyokan di Jawa Barat - Jamaludin, Ahmad; Nuraeni, Risti Dea (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2025)
Children are the nation’s next generation and play a vital role in sustainable development and the country’s future. The protection of children, including within the context of criminal law, is a fundamental aspect of building a holistic Indonesian human resource foundation based on Pancasila and the 1945 Constitution. This study analyzes the effectiveness of implementing diversion in resolving juvenile cases involving assault and collective violence in Bandung, West Java. The research aims to examine the implementation of the diversion concept within the juvenile criminal justice system, assess the effectiveness of rehabilitative approaches, evaluate legal protection mechanisms, identify the underlying factors behind juvenile delinquency, and formulate policy recommendations for improving child protection. A qualitative research approach was employed, with data collected through interviews at the Bandung Child Rights Advocacy Institute (Lembaga Advokasi Hak Anak/LAHA). Diversion plays a crucial role in Indonesia’s juvenile criminal justice system. The findings indicate that while diversion has been implemented, it continues to face various challenges, particularly concerning infrastructure and the interpretation of the Juvenile Criminal Justice System Law. Several obstacles hinder its success, including limited participation from victims and communities, as well as persistent negative stigma toward juvenile offenders. Therefore, further measures are needed to raise public awareness of the importance of diversion and to strengthen inter-institutional collaboration. The study suggests that enhancing the effectiveness of diversion requires a comprehensive approach involving multiple stakeholders.